موقف الشريعة من موانع الحمل - بالنور, نعيمة; غمام جريدي, عائشة; بن ناصر, جميلة (جامعة الوادي - University of Eloued, 2014)
Summary This includes research a topic of importance in terms of jurisprudence, in the door of worship, a«position that the law of contraception», this is considered of important things that need to know and a statement of its provisions We have divided this research into two sections and a conclusion Study of the first: to ensure the definition of some of the vocabulary of the title and the motives and means of contraception Study II: devoted to the rule of legitimate contraceptives: the rule of temporary barriers, sterilization, drop the fertilized egg, and the rule of contraception as it relates to birth control Conclusion: The most important results obtained during the study.
ليسانس